1986
DOI: 10.1152/ajpendo.1986.251.4.e431
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of central hyperglycemic effect of cholinergic agonists in fasted rats

Abstract: The influence of cholinergic agonists on central nervous system (CNS) regulation of blood sugar homeostasis was studied in fasted rats. When carbachol, muscarine, bethanechol, methacholine, or neostigmine was injected into the third cerebral ventricle, it caused a dose-dependent increase in the hepatic venous plasma glucose concentration. However, in the case of 1,1-dimethylphenyl-4-piperazinium iodide (DMPP) or nicotine, the level of hepatic venous glucose did not differ from that of the saline-treated contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…It is previously reported that the nonselective muscarine receptor agonists increase blood glucose levels, indicating that central muscarine receptors positively regulate blood glucose levels [37]. The present study showed that muscarinic M 1 receptor antagonist dicyclomine did not affect the blood glucose levels.…”
Section: Discussionsupporting
confidence: 51%
“…It is previously reported that the nonselective muscarine receptor agonists increase blood glucose levels, indicating that central muscarine receptors positively regulate blood glucose levels [37]. The present study showed that muscarinic M 1 receptor antagonist dicyclomine did not affect the blood glucose levels.…”
Section: Discussionsupporting
confidence: 51%
“…Although it has not yet been thoroughly clarified whether or not somatostatin itself directly affects the rates of either glucose uptake or glucose production (Cherrington et al ., 1977;Sacca et al, 1979), our previous report (Iguchi et al, 1986) demonstrated that the hyperglycemic response to endogeneously secreted epinephrine is not influenced by this constant somatostain infusion . Furthermore, bombesin-induced hyperglycemia was not observed in bilateral adrenalectomized rats with constant somatostatin infusion , supporting the theory that the hyperglycemic response to bobesin is dependent on the secretion of epinephrine.…”
Section: Discussionmentioning
confidence: 79%
“…We recently reported that neostigmine injected into the third cerebral ventricle stimulated the secretion of epinephrine, which in turn resulted in producing hyperglycemia in the absence of a rise in the plasma glucagon concentration during constant intravenous infusion of somatostatin (Iguchi et al, 1986). Thus, the present study was aimed to further examine whether bombesin-induced central hyperglycemia was due to secreted einephrine itself, or mediated via epinephrine-stimulated glucagon secretion.…”
mentioning
confidence: 92%
“…IRG was measured by radioimmunoassay according to the method described previously [5]. The plasma levels of epinephrine and norepinephrine were determined using high-performance liquid chromatography with electrochemical detector as described pre viously [6], After the experiments, the animals were killed and their brains were fixed with 20% formalin for histologic examination. Proper placement of the needles and the correctness of the lesioned areas was histologically confirmed [7].…”
Section: Methodsmentioning
confidence: 99%